2018
DOI: 10.1002/biot.201700771
|View full text |Cite
|
Sign up to set email alerts
|

Improved HCP Reduction Using a New, All‐Synthetic Depth Filtration Media Within an Antibody Purification Process

Abstract: Biologic manufacturing processes typically employ clarification technologies like depth filtration to remove insoluble and soluble impurities. Conventional depth filtration media used in these processes contain naturally-derived components like diatomaceous earth and cellulose. These components may introduce performance variability and contribute extractable/leachable components like beta-glucans that could interfere with limulus amebocyte lysate endotoxin assays. Recently a novel, all-synthetic depth filtrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Several previous studies have also demonstrated that hydrophobic interactions can be important for removal of some impurities based on results with solutions of different conductivity 12,16 or in the presence of a non‐ionic surfactant 11 . Recent studies using fully synthetic depth filter media (without any diatomaceous earth or perlite) show much higher binding of positively‐charged HCP, demonstrating the importance of electrostatic interactions 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have also demonstrated that hydrophobic interactions can be important for removal of some impurities based on results with solutions of different conductivity 12,16 or in the presence of a non‐ionic surfactant 11 . Recent studies using fully synthetic depth filter media (without any diatomaceous earth or perlite) show much higher binding of positively‐charged HCP, demonstrating the importance of electrostatic interactions 17 …”
Section: Introductionmentioning
confidence: 99%
“…11 Recent studies using fully synthetic depth filter media (without any diatomaceous earth or perlite) show much higher binding of positivelycharged HCP, demonstrating the importance of electrostatic interactions. 17 The objective of this study was to examine the HCP removal characteristics of the Pall PDH4 media, a model commercial depth filter containing diatomaceous earth with pore size from 15 to 0.5 μm that is of growing interest in mammalian cell culture clarification. Data were obtained with both mammalian cell culture fluid and with a series of model proteins with well-defined properties (chosen to match key HCP) to identify both the extent of protein binding and its dependence on the key physical characteristics of the individual proteins.…”
mentioning
confidence: 99%
“…In general, depth filters have already been adapted for high-density continuous culture systems (Oh, Choi et al 1994) and for the higher load titers. The newer synthetic depth filters also show higher clearance levels of host-cell derived impurities (Khanal, Singh et al 2018, Nguyen, Langland et al 2019. Therefore, these newer single-use depth filters offer an orthogonal option to viral clearance especially in a continuous process with longer processing times and increased impurity and overall titer profiles.…”
Section: Emerging Technologymentioning
confidence: 99%
“…[ 31,32 ] Functionalized depth filters with improved surface properties such as Zeta plus series from 3M and Millistak series from Merck have been reported to achieve both clarification and process impurity clearance in a single step. [ 33,34 ] Castro (2015) demonstrated that a synthetic depth filter with a hydrogel layer, modified with a quaternary amine, can clarify an IgG1 CHO cell harvest while reducing the level of process impurities. [ 35 ] In terms of HCP clearance, the modified depth filter performed seventeen times better than conventional cellulose‐based‐depth filters.…”
Section: Advances In Membrane Technology For Downstream Applicationsmentioning
confidence: 99%